Pengaruh Mekanisme Good Corporate Governance, Kinerja Keuangan, dan Struktur Modal terhadap Pengungkapan Sustainability Report - Amelia Kristianingrum; Fatmasari Sukesti; Nurcahyono Nurcahyono (Universitas Muhammadiyah Semarang, 2022)
This study aims to determine the effect of independent commissioners, audit committees, profitability, liquidity, and leverage on the disclosure of sustainability reports in manufacturing companies listed on the IndonesiaStock Exchange (IDX) in 2019-2021. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. This study uses a purposive sampling technique. The sample used in this study was 17 manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2021 period, so based on predetermined criteria, the number of samples was 51 samples. The analysis used in thisstudy is multiple regression analysis, classical assumption test and hypothesis testing using SPSS version 25 as a calculation tool. Based on the results given in this study, it shows that profitability and liquidity have an effect on firm value, while independent commissioners, audit committees and leverage have no effect on sustainability report disclosure. The predictive ability of the four variables on the sustainability report disclosure is 33.4% while the other 66.6% comes from other variables.Keywords: independent commissioner, audit committee, profitability, liquidity, and leverage on sustainability report disclosure.